LEGAL BASIS AND MAIN DIRECTIONS OF THE FOREIGN POLICY OF THE BPSR (TAMADDUN NURI JURNALI, 2024)
In this article, we will talk about the foreign policy of the Bukhara People's Soviet Republic and its legal foundations. Studying the socio-economic, political and cultural processes taking place in the world, the relations of mutual cooperation of the countries of the world is becoming one of the urgent issues of today. In the domestic and foreign policy of the countries of the world, issues of strengthening mutually beneficial cooperation, international harmony, wide economic and cultural cooperation are of particular importance.